2014
DOI: 10.1155/2014/643685
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Skin Crease versus Vertical Midline Incision versus Laparoscopy for Right Hemicolectomy: A Systematic Review—Current Status of Right Hemicolectomy

Abstract: Purpose. The right hemicolectomy may be conducted through laparoscopic or laparotomic surgery, transverse or midline incisions. The transverse laparotomy offers some advantages compared to the midline laparotomy and laparoscopy. A literature review was performed to evaluate the possible advantages of the transverse incision versus midline incision or laparoscopic right hemicolectomy. Methods. A systematic research was performed in Medline, Embase, Cochrane Central Register of Controlled Trials, CINAHL, BioMed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
4
4
0
Order By: Relevance
“…Comparable finding was also reported from Nepal [52]. The potential reason may be that, having vertical skin incision is associated with involving more areas, delayed wound healing, higher risk of wound dehiscence, that will put the mothers for risk of developing SSI following the procedure [53,54].…”
Section: Discussionsupporting
confidence: 51%
“…Comparable finding was also reported from Nepal [52]. The potential reason may be that, having vertical skin incision is associated with involving more areas, delayed wound healing, higher risk of wound dehiscence, that will put the mothers for risk of developing SSI following the procedure [53,54].…”
Section: Discussionsupporting
confidence: 51%
“…Several authors have compared functional and oncological outcomes of laparoscopic right hemicolectomy to the open procedure; however, only a few studies have evaluated the transverse‐incision approach . Our data are similar to the results of the retrospective series by Lohsiriwat et al .…”
Section: Discussionsupporting
confidence: 86%
“…Laparoscopic versus transverse and midline right‐sided colectomy has also been retrospectively investigated by Tanis et al . and Lorenzon et al, and the issue was addressed in a systematic review by Santoro et al . Both Tanis and Lorenzon concluded that laparoscopic and transverse open right hemicolectomy are equivalent and have significant better short‐term outcomes compared to the midline open procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was in line with study conducted in Nepal [45]. The potential reason may be having vertical skin incision is associated with involving more areas, delayed wound healing, higher risk of wound dehiscence, that will put the women for risk of developing SSI following the procedure [46,47].…”
Section: Factors Associated With Ssi After Cesarean Sectionsupporting
confidence: 88%